Divine bud : testimonies of God's intervention - Mutaka, Philippe (Langaa Research & Publishing CIG ; Distributed in and outside N. America by African Books Collective, 2012)
This book presents material on ethnography; more specifically, it exposes events where African individuals deal with the supernatural. This book contains stories such as the reaction to the death of a child whose surgical operation was considered an answer to prayers to God, how African students have dealt with evil spirits in their lives, how African people have experimented the phenomenon of "miracle" with their specific religious background that merges imported religions (Christian and Islam) and their traditional cultural religious beliefs. The material is also of interest to readers concerned with the need for dialogue between religions for the purpose of finding solutions to conflicts arising in the modern world. The book is thought-provoking. See, for example, what happens when a Muslim faces Jesus Christ. Mevoutsa's testimony in a later chapter explores the way Africans attached to their traditional cultures believe that God may use tradition healers to manifest his presence among his creatures.